2022
DOI: 10.3390/bs12090316
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise and Undergraduate Students’ Subjective Well-Being: Mediating Roles of Basic Psychological Need Satisfaction and Sleep Quality

Abstract: This study aimed to examine the association between physical exercise and subjective well-being among undergraduate students, as well as its underlying mechanism—the potential mediating roles of basic psychological need satisfaction and sleep quality—from the perspective of self-determination theory. A sample of 770 undergraduate students (mean age was 19.90 ± 1.15 years old; 464 women) were recruited voluntarily to complete a set of measures examining physical exercise habits, psychological need satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Speci cally, physical activity indirectly enhances subjective well-being by ful lling basic psychological needs. This underscores a signi cant positive correlation between physical activity and the basic psychological needs of college students, consistent with previous research ndings [40][41] [42] .…”
Section: The Mediating Role Of Basic Psychological Needssupporting
confidence: 92%
“…Speci cally, physical activity indirectly enhances subjective well-being by ful lling basic psychological needs. This underscores a signi cant positive correlation between physical activity and the basic psychological needs of college students, consistent with previous research ndings [40][41] [42] .…”
Section: The Mediating Role Of Basic Psychological Needssupporting
confidence: 92%
“…Consequently, we posited that behaviors aimed at mitigating negative emotions or fulfilling psychological needs may bolster an individual's subjective well-being (53). In addition to physical activity, various methods can be employed to boost subjective well-being, including parental or social support (54,55), maintaining healthy sleep patterns (56), and avoiding a range of health-risk behaviors (47).…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone addiction is most likely to occur when an individual’s three basic psychological needs are less satisfied in the real world and more satisfied in the virtual world. It has been shown that physical exercise has a significant positive predictive effect on basic psychological need satisfaction in college students [ 51 ]. Physical exercise reduces the possibility of smartphone addiction in college students by enhancing the satisfaction of their basic psychological needs.…”
Section: Discussionmentioning
confidence: 99%